Flavonoids in vegetable foods commonly consumed in Brazil and estimated ingestion by the Brazilian population - Arabbi, Paola R; Genovese, Maria Inés; Lajolo, Franco M (Journal of agricultural and food chemistry, 2004)
The objective of this work was to quantify the flavonoids present in foods most commonly consumed by the Brazilian population. The predominant flavonoids found in largest abundance in all of the analyzed vegetables were glycosides of quercetin. In lettuce, a small amount of luteolin was also detected. In sweet pepper, quercetin and luteolin were both present. White onion [48-56 mg/100 g of fresh weight (FW), expressed as aglycon], red onion (40-100 mg/100 g of FW), red lettuce (67-67.2 mg/100 g of FW), arugula (41-118 mg/100 g of FW), and chicory (18-38 mg/100 g of FW) were highest in total flavonoids. In fruits, the highest concentrations of flavonoids were found in the peel (125-170 mg/100 g of FW) and pulp (35-44 mg/100 g of FW) of oranges and in some apple varieties (14-36 mg/100 g of FW). Variability in flavonoid content due to time of harvesting was high for leafy vegetables and red onions. The estimated ingestion by Brazilian population ranged from 60 to 106 mg/day.